The effectiveness of breakfast recommendations on weight loss: a randomized controlled trial. Issue 2 (4th June 2014) - Dhurandhar, Emily J; Dawson, John; Alcorn, Amy; Larsen, Lesli H; Thomas, Elizabeth A; Cardel, Michelle; Bourland, Ashley C; Astrup, Arne; St-Onge, Marie-Pierre; Hill, James O; Apovian, Caroline M; Shikany, James M; et al.
ABSTRACT: Background: Breakfast is associated with lower body weight in observational studies. Public health authorities commonly recommend breakfast consumption to reduce obesity, but the effectiveness of adopting these recommendations for reducing body weight is unknown. Objective: We tested the relative effectiveness of a recommendation to eat or skip breakfast on weight loss in adults trying to lose weight in a free-living setting. Design: We conducted a multisite, 16-wk, 3-parallel-arm randomized controlled trial in otherwise healthy overweight and obese adults [body mass index (in kg/m 2 ) between 25 and 40] aged 20–65 y. Our primary outcome was weight change. We compared weight change in a control group with weight loss in experimental groups told to eat breakfast or to skip breakfast [no breakfast (NB)]. Randomization was stratified by prerandomization breakfast eating habits. A total of 309 participants were randomly assigned. Results: A total of 283 of the 309 participants who were randomly assigned completed the intervention. Treatment assignment did not have a significant effect on weight loss, and there was no interaction between initial breakfast eating status and treatment. Among skippers, mean (±SD) baseline weight-, age-, sex-, site-, and race-adjusted weight changes were -0.71 ± 1.16, -0.76 ± 1.26, and -0.61 ± 1.18 kg for the control, breakfast, and NB groups, respectively. Among breakfast consumers, mean (±SD) baseline weight-, age-, sex-, site-, and race-adjusted weight changes were -0.53 ± 1.16, -0.59 ± 1.06, and -0.71 ± 1.17 kg for the control, breakfast, and NB groups, respectively. Self-reported compliance with the recommendation was 93.6% for the breakfast group and 92.4% for the NB group. Conclusions: A recommendation to eat or skip breakfast for weight loss was effective at changing self-reported breakfast eating habits, but contrary to widely espoused views this had no discernable effect on weight loss in free-living adults who were attempting to lose weight. This trial was registered at clinicaltrails.gov as NCT01781780.